Answer:
see explanation
Explanation:
Given
6a² - a - 5 = 0
Consider the factors of the product of the a² term and the constant term which sum to give the coefficient of the a- term.
product = 6 × - 5 = - 30 and sum = - 1
The factors are - 6 and + 5
Use these factors to split the a- term
6a² - 6a + 5a - 5 = 0 ( factor the first/second and third/fourth terms )
6a(a - 1) + 5(a - 1) = 0 ← factor out (a - 1) from each term
(a - 1)(6a + 5) = 0
Equate each factor to zero and solve for a
a - 1 = 0 ⇒ a = 1
6a + 5 = 0 ⇒ 6a = - 5 ⇒ a = -
Solution set = { 1, -
}